2009
DOI: 10.1176/jnp.2009.21.2.216
|View full text |Cite
|
Sign up to set email alerts
|

Apathy Due to Cerebrovascular Accidents Successfully Treated With Methylphenidate: A Case Series

Abstract: Apathy has been observed in various types of neuropsychiatric illness, including degenerative, traumatic, and cerebrovascular. In this article, the authors describe the neurobiology of cerebrovascular induced apathy and its treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…That study found a significant improvement in AES scores after 12 weeks of treatment. Other case reports have described using MTP to effectively treat apathy in the depressed population [135,136], the Parkinson's population [131], cerebrovascular accident patients [139], and patients with idiopathic normal pressure hydrocephalus [133]. Another recent RCT reported that apathy scores improved significantly in depressed patients who were treated with MTP in combination with an antidepressant, compared to patients using the antidepressant alone [138].…”
Section: Pharmacotherapy (Table 2)mentioning
confidence: 99%
“…That study found a significant improvement in AES scores after 12 weeks of treatment. Other case reports have described using MTP to effectively treat apathy in the depressed population [135,136], the Parkinson's population [131], cerebrovascular accident patients [139], and patients with idiopathic normal pressure hydrocephalus [133]. Another recent RCT reported that apathy scores improved significantly in depressed patients who were treated with MTP in combination with an antidepressant, compared to patients using the antidepressant alone [138].…”
Section: Pharmacotherapy (Table 2)mentioning
confidence: 99%
“…Some aver that apathy responds better to cholinesterase inhibitors, while a reduction in irritability and agitation may be more closely associated with memantine treatment (Cummings et al 2008). The successful use of methylphenidate to treat stroke-induced apathy has been reported (Spiegel et al 2009). Atypical antipsychotics given to patients with schizophrenia (clozapine alone or with mirtazapine, respiradone, olanzapine) as well as certain antidepressants (buproprion) and psychostimulants (amphetamine, methylphenidate, and modafinil) used in the treatment of various brain disorders are also said to have benefited apathy (Marangell et al 2002;Corcoran et al 2004;Daiello 2007;Padala et al 2007Padala et al , 2010.…”
Section: Current Therapeutic Approachesmentioning
confidence: 99%
“…It is believed to be due to malfunction of the brain's motivational circuitry . Research implies myriad causes, including basal ganglia dysfunction as seen in Parkinson disease, prefrontal and/or basal ganglia damage due to stroke, and endocrine dysfunction following a tumor or traumatic brain injury . Apathy is important to study because poorer outcome has been identified in those with apathy among numerous clinical populations.…”
Section: Introductionmentioning
confidence: 99%